Why is reporting quality improvement so hard? A qualitative study in perioperative care - Mary Dixon-Woods; Emma Leanne Jones; Graham P Martin (BMJ Open)
Objectives Quality improvement (QI) may help to avert or mitigate the risks of suboptimal care, but it is often poorly reported in the healthcare literature. We aimed to identify the influences on reporting QI in the area of perioperative care, with a view to informing improvements in reporting QI across healthcare.Design Qualitative interview study.Setting Healthcare and academic organisations in Australia, Europe and North America.Participants Stakeholders involved in or influencing the publication, writing or consumption of reports of QI studies in perioperative care.Results Forty-two participants from six countries took part in the study. Participants included 15 authors (those who write QI reports), 12 consumers of QI reports (practitioners who apply QI research in practice), 11 journal editors and 4 authors of reporting guidelines. Participants identified three principal challenges in achieving high-quality QI reporting. First, the broad scope of QI reporting—ranging from small local projects to multisite research across different disciplines—causes uncertainty about where QI work should be published. Second, context is fundamental to the success of a QI intervention but is difficult to report in ways that support replication and development. Third, reporting is adversely affected by both proximal influences (such as lack of time to write up QI) and more distal, structural influences (such as norms about the format and content of biomedical research reporting), leading to incomplete reporting of QI findings.Conclusions Divergent terminology and understandings of QI, along with existing reporting norms and the challenges of capturing context adequately yet succinctly, make for challenges in reporting QI. We offer suggestions for improvement.